Analysis of Carbon Emission Source Control using Seven Tools - Taufik Hidayat; Tasdik Darmana; Sulastri Sulastri; Alyssa Azizah; Mochamad Rizqy (JUMANTARA: Jurnal Manajemen dan Teknologi Rekayasa, 2026)
Climate change mitigation requires higher education institutions to identify and control carbon emission sources generated by their operational activities. Previous studies in university environments have generally focused on carbon footprint quantification without systematically analyzing the root causes of emissions and identifying priority improvement actions. Therefore, this study proposes the integration of Carbon Footprint assessment with the Seven Tools approach within a Statistical Process Control (SPC) framework to identify dominant emission sources, analyze root causes, and formulate emission reduction strategies. The study employed a quantitative descriptive method using one-year operational data consisting of electricity consumption and fuel usage. Carbon emissions were calculated based on IPCC emission factors and subsequently analyzed using selected Seven Tools, namely histogram, Pareto diagram, and fishbone diagram. The results indicate that electricity consumption (Scope 2) contributed 1,112,996.46 kg CO₂/year or 98.23% of total emissions, whereas fuel consumption (Scope 1) accounted for only 20,066.67 kg CO₂/year or 1.77%. Fishbone analysis revealed that the dominant causes originated from human behavior, inefficient equipment, lack of energy management procedures, and dependence on fossil-based electricity. The novelty of this study lies in applying Seven Tools, traditionally used for quality improvement, to carbon emission management in higher education institutions. The findings provide practical guidance for energy management programs and demonstrate that electricity efficiency and renewable energy adoption could potentially reduce institutional carbon emissions by more than 20–30%.